Benefit cost analysis in appraisal and planning projects of higher learning institutions - Javed, M.S. (2013)
Benefit Cost Analysis is a technique used for assessing the impacts of proposed actions in a project planning process. Under available resource constraints, accurate Benefit Cost Analysis provides a better economic choice among the projects. The main objective of the study is to address issues of Benefit Cost Analysis in project planning processes. A case study of the higher learning institution project of Pakistan is carried out wherein application and implications of Benefit Cost Analysis upon the project are evaluated and discussed. This study highlighted the significance of the correct estimation of benefits and costs in project appraisal and planning. For a more comprehensive appraisal and realistic outcomes, consideration should be given to the determination of accurate benefits and costs of a project Â© 2013 IEEE.